Chemical Radiation and Soret Effects on Unsteady MHD Convective Flow of Jeffrey Nanofluid Past an Inclined Semi-Infinite Vertical Permeable Moving Plate - Raju, Konduru Venkateswara; Mohanaramana, Ravuri; Reddy, S. Sudhakar; Raghunath, Kodi (Communications in Mathematics and Applications, 2023)
An unsteady, MHD incompressible water-based Jeffrey nanofluid (Cu and TiO2) flow across a stretched sheet in a transverse magnetic domain, thermic radiation, and Soret effects are examined in this article. For each physical parameter, the governing differential equalisations are converted into a set of nonlinear associated standard differential equalisations, translated utilising a perturbation approach with suitable limit essentials for the governing differential equations. The solution for the governing nonlinear boundary value concern is conveyed based on the perturbation technique throughout the complete range of material parameters. The impacts of numerous biological factors on the dimensionless velocity, temperature, concentration, and pressure silhouettes are graphically displayed and thoroughly examined. It is possible to gain favourable comparisons with formerly publicised work on several particular topic situations. Finally, numerical significances of material portions, such as the local skin-friction specification, the Nusselt numeral, and the Sherwood digit, are provided in tabular form, allowing easy comparison.